Analysis of Contact force optimization for a hybrid manipulator. Issue 1 (June 2021) - Canguo, Zhang; Shaolei, Wang; Yi, Lu; Xiaoyu, Ni; Chunhua, Zhu
Abstract: A novel hybrid manipulator is designed. Based on the fact that the sum of the external force vector for the object is zero, the criterion of the stability of the object is derived. The formula for calculating contact force of fingers was deduced by matrix theory. The maximum frictional force was taken as boundary condition, then the contact force of fingers was optimized. The advanced CAD software was used to simulate the process of grasping the object. The stability of the object at a certain time was verified. Finally, the contact force between fingers and objects was optimized. It provides a theoretical basis for the application of the hybrid manipulator.